The salivary scavenger and agglutinin binds MBL and regulates the lectin pathway of complement in solution and on surfaces - Parnov Reichhardt, Martin; Loimaranta, Vuokko; Thiel, Steffen; Finne, Jukka; Meri, Seppo; Jarva, Hanna (Frontiers in Immunology, 2012)
The scavenger receptor cysteine-rich (SRCR) protein SALSA, also known as gp340, salivary agglutinin (SAG) and deleted in malignant brain tumor 1 (DMBT1), is a 340 kDa glycoprotein expressed on mucosal surfaces and secreted into several body fluids. SALSA binds to a broad variety of microbes and endogenous ligands, such as complement factor C1q, surfactant proteins D and A (SP-D and SP-A) and IgA. Our search for novel ligands of SALSA by direct protein-interaction studies led to the identification of mannan binding lectin (MBL) as a new binding partner. We observed that surface-associated SALSA activates complement via binding of MBL. On the other hand, soluble SALSA was found to inhibit C. albicans-induced complement activation. Thus, SALSA has a dual complement regulatory function. It activates the lectin pathway when bound to a surface and inhibits it when free in the fluid-phase. These activities are mediated via a direct interaction with MBL.